ANALISIS KETIDAKSESUAIAN SUSUNAN FORMULIR REKAM MEDIS PADA PROSES ASSEMBLING (Analysis of Inconsistency in the Arrangement of Medical Record Forms in the Assembling Process) - Aprilifania Silvina Wahyudi; Enny Mar'atus Sholihah (Rena Cipta Mandiri, 2026)
Orderly medical record management is essential in supporting the quality of health services in hospitals. One stage in medical record management is the assembling process, which aims to arrange medical record forms according to the order listed in the medical record table of contents. However, in practice, inconsistencies in the arrangement of medical record forms are still found and may hinder subsequent document management processes. This study aims to analyze the inconsistency in the arrangement of medical record forms in the assembling process. This research used a descriptive method with an observational approach on inpatient medical record documents. Data were collected by observing 50 medical record documents for three weeks during February to March 2026. The results showed that 40 medical record documents (80%) were not arranged according to the order listed in the medical record table of contents, while 10 documents (20%) were arranged appropriately. The inconsistency in document arrangement can cause difficulties in further document management processes such as document sorting and storage. Therefore, improvement efforts are needed by providing visual guidance media such as a poster of the medical record form sequence to assist staff in arranging medical record documents systematically.